The Role of News Source Certification in Shaping Tweet Content: Textual and Dissemination Patterns in Brazil's 2022 Elections - Fonseca, Luis Guilherme G. Da; Ferreira, Carlos Henrique Gomes; Reis, Julio Cesar Soares Dos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Social media’s rise has reshaped information sharing and consumption, particularly in elections, resulting in more toxic content, like hate speech. Problem: While there are studies on news content on social media, they overlook the influence of external news sources, especially uncertified sources in the Brazilian context, on the spread of toxic and extremist content on Twitter/X. This gap makes it difficult to fully understand their role in the dissemination of information on social media platforms. Solution: This study investigates how different journalistic sources, certified or not by competent bodies, influence the nature and dissemination of tweets related to the Brazilian elections of 2022. In particular, it examines the influence of the toxic and emotional content of headlines on the amplification of tweets by users. IS Theory: This research draws on the Social Media Engagement (SME) theory, which emphasizes the role of user interaction and external elements in shaping social media communication and engagement. Method: We employ natural language processing techniques to analyze the toxicity and sentiment of tweets and their associated headlines, including quantitative and descriptive analysis of the content of tweets in relation to news sources. Summarization of Results: The results show a dominance of negative and toxic tweets, which are significantly shaped by the type of headlines and the certification of sources. Headlines from non-certified sources tend to generate toxic tweets, which indicates a tendency to spread extremist content. Contributions and Impact in the area of SI: Our findings shed light on the potential of integrating principles of social media engagement and online news production into information systems to create a better and healthier informative online environment.